APLICAÇÃO DA DISTRIBUIÇÃO BURR XII NA ANÁLISE DO TEMPO ATÉ A PRIMEIRA POSTURA DE CODORNAS - PERALTA, Danielle; MAZUCHELI, Josmar; EMANUELLI, Isabele Picada; ROSSI, Robson Marcelo (Brazilian Journal of Biometrics, 2017)
Generally, in survival analysis the observed response is the time elapsed between the baseline and the occurrence of a particular event. In this paper the response variable describes the number days elapsed between birth and the first posture (event) of quails submitted to two treatments. The main objective is to select the best probability distribution to describe the behavior of the age (in days) to the first posture. For all groups, given the nature of the response, the probability distributions were considered: Burr XII, Gamma, Inverse Gaussian, Lognormal, Weibull and Log-Logistic. For all distributions were estimated the average time and the most probable time for the first posture. Analytical procedures and graphics, used as discrimination tools, showed that the distribution Burr XII is the most appropriate to describe the response variable. The choice of a probability distribution that efficiently describe the phenomenon under study have implications on animal management and consequently in sustainability of production.